"Anthropogens" in Lifestyle Medicine. (May 2015) - Egger, Garry; Colquhoun, David; Dixon, John
Chronic disease epidemiology currently lacks the mono-causal focus germ theory provides infectious diseases. However, the discovery of a form of low-grade, systemic, and chronic inflammation ("metaflammation) underlying many, if not all, chronic diseases induced by a range of stimulants labeled "anthropogens" may help change this. Anthropogens are "man-made environments, their by-products, and/or lifestyles encouraged by these, some of which are detrimental to human health." While an exhaustive list of anthropogens associated with chronic disease may be as elusive as a comprehensive list of "germs" with the potential to cause infection, a broad taxonomy provides a focus for the practice of lifestyle medicine. Such a list is considered here under the acronym NASTIE ODOURS.